Effects of freezing and location within the beef longissimus muscle (strip loin steak) on tenderness - R.R. Timm; John A. Unruh; Michael E. Dikeman; Melvin C. Hunt; John E. Boyer; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 2002)
Twenty-four USDA Select strip loins (IMPS 180) were aged (32°F) until 14 days postmortem and fabricated into longissimus muscle (strip loin) steaks (1-in. thick). Then, steaks were either cooked or stored at −20°F for an additional 17 days before they were thawed and cooked. Cores and sensory panel samples were removed from the medial, center, and lateral sections of each steak and locational identify maintained. In addition, a random composite of cubes from an entire steak was used for a sensory panel evaluation. Previously frozen steaks had lower Warner-Bratzler shear force (WBSF) values, less cooking loss, and a shorter cooking time than fresh (non-frozen) steaks; however, no difference was found for combined thawing and cooking loss. Cores from the medial section of steaks had lower WBSF values than cores from the center section. A sensory panel found that the medial section was more tender than the lateral section and had less detectable connective tissue than the center or lateral sections or samples taken at random. The center and random treatments were juicer than the lateral section. Highest correlations between sensory panel tenderness and WBSF were obtained when the medial and lateral sections were averaged (r=−0.74, r=−0.69) and when all three sections were averaged (r=−0.70, r=−0.69) for fresh and frozen WBSF steaks, respectively. Freezing lowered WBSF values and the medial section of the steak was the most tender. An awareness of these results and potential procedural artifacts must be considered when handling and sampling steaks, and interpreting results.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Longissimus dorsi; Freezing; Steaks; Tenderness